2022
DOI: 10.3389/fpubh.2022.1038516
|View full text |Cite
|
Sign up to set email alerts
|

The effect of residential environment satisfaction on depression in the elderly: Focusing on the mediating effect of stress

Abstract: This study aimed to determine the mediating effect of stress on the relationship between residential environment satisfaction and feelings of depression in the elderly. To achieve the purpose of the study, the researcher personally conducted interviews with 250 senior citizens residing in Jeollanam-do, South Korea, from October to November 2019. SPSS version 27.0 and Hayes' PROCESS ver. 4.0 were used for data analysis. As a result of testing the research hypothesis, a partial mediating effect of stress on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Economically developed cities have extensive pension resources and su cient economic capacity to increase nancial investment, awareness of pension services, and pension subsidies. 30,44 Furthermore, implementing preferential policies and increasing attention toward and the accessibility of pension services results in a higher pension demand. Moreover, high-income individuals were accepted in the pension market and had access to high-quality and high-end pension resources.…”
Section: Dissimilaritiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Economically developed cities have extensive pension resources and su cient economic capacity to increase nancial investment, awareness of pension services, and pension subsidies. 30,44 Furthermore, implementing preferential policies and increasing attention toward and the accessibility of pension services results in a higher pension demand. Moreover, high-income individuals were accepted in the pension market and had access to high-quality and high-end pension resources.…”
Section: Dissimilaritiesmentioning
confidence: 99%
“…Furthermore, this study observed that the concern for an endowment environment was prominent as agefriendliness directly affected residents' sense of residential security, residential satisfaction, and physical and mental health. 30 However, the construction of a livable environment for old adults in China lags signi cantly, with a signi cant gap between urban and rural areas, resulting in insigni cant improved residential satisfaction of older adults. 31 Hence it is urgent to build a friendly environment for older adults.…”
Section: Signi Cant Demand For Healthy Aging Servicesmentioning
confidence: 99%